Robotic-assisted thoracoscopic surgery in children: a safe approach to remove thoracic tumors - Palo, F.; Brenco, G.; Torre, M.; Wolfler, A.; Reali, S.; Avanzini, S.; Mattioli, G. (Frontiers in Pediatrics, 2025)
IntroductionRobotic-assisted thoracoscopic surgery (RATS) in children remains a challenge, particularly in oncological cases. This study aims to provide practical and useful insights to enhance the safety and efficacy of this surgical approach.MethodsThis is a single-center retrospective analysis conducted over a four-year period (2020–2025), including all pediatric patients (aged 0–18 years) who underwent RATS for thoracic tumor resection with a minimum follow-up of six months.ResultsWe reviewed 20 cases from pediatric patients who underwent RATS for the removal of thoracic tumors. One patient required a second procedure, totaling 21 surgeries. Neuroblastic tumors were the most frequently treated tumor (50%). The youngest patient was 16 months old, with a median age at surgery of 5 years (IQR: 14–4). The smallest patient weighed 11 kg at surgery with a median weight at surgery of 25 kg (IQR: 49.5–17). A maximum of four trocars were used. Selective ventilation was required only in 5 cases. The median operative time was 135 min (IQR: 100–180). The largest resected lesion measured 63 × 45 × 94 mm and was removed from a 3-year-old patient. Complete tumor resection was achieved in 19 patients. Conversion to open surgery was necessary in 4 cases (19%), primarily due to the need for manual tumor manipulation to ensure proper delineation. Two complications (10%) were recorded, both cases of chylothorax (Clavien-Dindo grades 2). Two patients died due to Ewing sarcoma recurrence, while all others are off therapy and in follow-up; five patients (25%) received adjuvant treatment after surgery.DiscussionRobotic surgery is a viable and safe option for pediatric thoracic tumors in selected cases. In our experience, the technique appeared suitable for all the types of tumors we have been treating, though broader applicability remains to be confirmed. However, RATS should be carefully considered in cases involving deeply infiltrating intrapulmonary lesions, major vascular involvement, or tumors requiring rib resection. Additionally, we believe single-lung ventilation is generally unnecessary unless intrapulmonary tumors are present.